MAGNETIC LEVITATION TECHNOLOGY IN TRAINS: A SYSTEMATIC LITERATURE REVIEW FROM 2018 TO 2023 - ESPEJO-PEÑA, DENNIS ALBERTO (2024)
THE PURPOSE OF THIS SYSTEMATIC REVIEW IS TO OFFER A COMPILATION OF INFORMATION ABOUT THE TECHNOLOGICAL ADVANCES OF MAGNETIC LEVITATION APPLIED IN TRAINS FROM THE YEARS 2018 TO 2023. TO COLLECT INFORMATION, USED HE SEEKER SCOPUS, WHERE WE FIRST STARTED WITH AN UNFILTERED SEARCH FOR THE TOPIC TO BE INVESTIGATED, THUS OBTAINING A TOTAL OF 2392DOCUMENTS; AFTER APPLYING A SERIES OF FILTERS THROUGH THE PRISMA SELECTION PROCESS, A TOTAL OF 114 DOCUMENTS THAT WERE USED FOR THE FINAL DEVELOPMENT THAT OF THE SYSTEMATIC REVIEW. FINALLY, IT IS CONCLUDED THAT MAGNETIC LEVITATION APPLIED TO TRAINS OFFERS A SERIES OF ADVANTAGES IN TERMS OF EFFICIENCY, SPEED, AND SUSTAINABILITY. HOWEVER, CONTINUED INVESTMENT AND DEVELOPMENT IS STILL REQUIRED TO OVERCOME CHALLENGES AND ACHIEVE WIDER IMPLEMENTATION IN RAIL TRANSPORT GLOBALLY. © 2024 LATIN AMERICAN AND CARIBBEAN CONSORTIUM OF ENGINEERING INSTITUTIONS. ALL RIGHTS RESERVED.